Pengaruh Kemampuan, Kecakapan Dan Keterampilan Terhadap Kinerja Auditor di Kota Metro - Agustuti Handayani (Universitas Bandar Lampung (UBL), 2015)
Purpose of this study is aim of this research is to investigate and analyze: (1) Effect of Traffic Inspectorate auditors on the effectiveness of supervision at the local government district of Bandar Lampung. (2) Effect of the auditors on the effectiveness of supervision skills Inspectorate in Bandar Lampung local government district. (3) Effect of auditors on the effectiveness of supervision skills Inspectorate in Bandar Lampung local government district. And (4) Effect of abilities, aptitudes and skills for effective supervision of the Inspectorate in the local government district of Bandar Lampung. Research was conducted at Inspectorate Bandar Lampung. Data were analyzed using multiple linear regression analysis.The results showed that: 1) partially shows that the variables affect the auditor's ability to control the effectiveness of the Local Government Inspectorate in Bandar Lampung. This shows that the higher the ability of auditors in terms of knowledge, experience and education will further increase the effectiveness of supervision Inspectorate. 2) partially shows that the variables affect the effectiveness of auditor competence oversight on Local Government Inspectorate Bandar Lampung. This shows that the higher the auditor skills in this response and communicative work will further improve the effectiveness of supervision Inspectorate. 3) partially shows that skill variables affect the effectiveness of the supervisory auditor at the Government Inspectorate Bandar Lampung. This shows that the higher the auditor's skills and expertise in this regard in the speed of work would increase the effectiveness of supervision Inspectorate. 4) Simultaneously indicates that the variable ability, aptitude and skills auditor jointly influence the effectiveness of the Local Government Inspectorate supervision Bandar Lampung.